A Review on Reducing Grain Boundaries and Morphological Improvement of Perovskite Solar Cells from Methodology and Material‐Based Perspectives. Issue 5 (26th September 2019) - Choi, Hyuntae; Choi, Kyoungwon; Choi, Yelim; Kim, Taewan; Lim, Seyeong; Park, Taiho
Abstract: Perovskite solar cells (PSCs) have achieved 25.2% of their certified efficiency and emerged as up‐and‐coming energy‐harvesting candidates owing to their superior properties. However, perovskite films are mainly polycrystalline films, and thus, the formation of grain boundaries (GBs) is inevitable. Since GBs have numerous defect sites that provide a channel for ion migration, reducing GBs is highly significant for achieving high efficiency and long‐term stability of PSCs. To this end, researchers have made efforts to produce a large crystal‐based perovskite film with reduced GBs. In this study, various methods that decrease GBs and enhance the morphology of perovskites are summarized and categorized into methodology‐ and material‐based approaches. Furthermore, a future research direction to produce high‐quality and large grain‐based perovskite film is also proposed. Abstract : Various deposition methodologies and additives are summarized in this review. Deposition methods and introduced additives largely influence the morphology of perovskite crystals, improving both device efficiency and stability. This review is aimed to present an overview of perovskite fabrication methods and additives introduced so far. Lastly, the existing challenges and outline for future research are provided.